HOW EASE OF PAYMENT AND DISCOUNT IN E-COMMERCE INFLUENCE ON CONSUMER PURCHASE DECISIONS - Ety Nurhayaty; Dede Suleman; Mohamad Trio Febriyantoro; Ida Zuniarti; Sri Rusiyati; Sofyan Marwansyah; Aprilia Puspasari; Lukman Hakim (RADJA PUBLIKA, 2023)
The growth of e-commerce is very rapid in today's era, giving rise to intense competition and efforts to increase consumers in an e-commerce are not easy efforts. Therefore, many advantages are now being offered by e-commerce, including the ease of payment and the many discounts that are provided. So research on these two variables is important to see the effect on consumer purchasing decisions. In this study using 100 sample 3 variables and 15 indicators and using SPSS analysis tools. The results showed that the ease of payment or the ease of payment has an effect on purchasing decisions and discounts also have an effect on consumer purchasing decisions. Therefore efforts to increase ease of payment and discounts are the right strategy for e-commerce to increase sales.